Effects of heavy resistance training on short-distance sprint performance - Meinhold, Marius (2019)
Introduction. Short-distance sprinting is a critical component of physical performance in many sports. Substantial evidence associates sprint performance over the first 30m with the level of maximal strength of an individual. Several authors question the transfer of heavy resistance training (RT) to highly dynamic motor tasks like sprints or jumps. The majority of research focusses on large muscle groups acting as hip and knee extensors during the sprint. A recent study suggests a significant correlation between the maximal strength of the plantarflexors and short-distance sprint performance. The purpose of this study was to examine the effects of six weeks of heavy RT of the plantarflexors in addition to a general RT programme on short-distance sprint times and vertical and horizontal jump performance. Methods. In total, twenty-one male subjects of varying training status were randomly allocated to an experimental group (EXP; n = 11) and a control group (CON; n = 10). The groups were matched for their one repetition maximum (1RM) in the standing calf raise (SCR) relative to their body mass and their 30m sprint time. Both groups performed 1RM testing of the deep squat and SCR, squat jumps (SJ), countermovement jumps (CMJ), standing long jumps (SLJ) and drop jumps (DJ) and 30m sprints on two separate testing days prior to and after the intervention. The subjects participated in supervised RT sessions including deep squats, bench press, chin ups, SCR (EXP) and overhead press (CON) twice weekly over six weeks. Additionally, the weekly schedule included two aerobic endurance sessions and one speed session. Results. The groups did not differ significantly from each other any parameter at the start of the intervention. Both groups significantly improved their 1RM in the squat (EXP +13.1%; CON +17.6%) and in the SCR (EXP +11.8; CON +14.8%). The differences between the groups were not significant. The statistical analysis revealed no significant changes in any other parameter. Conclusion. Heavy resistance training performed twice weekly is sufficient to induce meaningful, significant improvements in maximal strength in the deep squat and the SCR. The lack of significant differences between the groups indicates that the SCR 1RM is potentially invalid in detecting differences in plantarflexion strength. Despite the addition of a weekly session comprising sprints and jumps, the intervention failed to induce statistically significant changes in any other parameters but the 1RM tests. The results implicate that heavy RT can be performed twice weekly without negatively affecting sprint and jump performance.